M’addib s and Migrant Laborers: Migration from Ottoman Trablus al-Gharb to Djerba, Tunisia in the Early 20th Century - Love Jr, Paul M. (International Journal of Middle East Studies, 2025)
This article follows the history of migration from the mountain villages of the Jebel Nafusa in Ottoman Trablus al-Gharb (in today’s northwestern Libya) to the southern Tunisian island of Djerba in the early 20th century. It situates this local history of migration within the broader framework of Maghribi migration both before and during the colonial era in Libya (1911–43), while tracing the histories of two categories of migrants, in particular, manual laborers and Qur’an teachers (m’addib-s). The article makes three claims: (1) Nafusi migration was as much the result of local historical circumstances as it was a response to colonialism; (2) the historical experience of migration of Nafusis differed according to social class; and (3) local circumstances shaped the dynamics of migrant integration in the Maghrib. In doing so, I demonstrate how Nafusi migration to Djerba both conforms to and diverges from the larger history of late Ottoman and colonial-era migration in Tunisia. By shifting the focus away from the colonial moment, I make the case for foregrounding longer-term regional connections and migrations that linked different spaces across the Maghrib and also attend to local histories and what they offer in the way of caveats and exceptions.
Keywords: Bumas'ud, mosquée (Ajim, Djerba); Emigration -- Djebel Nefousa -- Djerba; Enseignement -- Djerba -- 1881-1956; Malāq, mosquée (Oualegh, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

ملامح الحركة الفكريّة في جربة: (منطقة سدويكش) : مع تحقيق نصوص مخطوطة 11ه/17م - بن يحياتن, ساسي بن عمر (اباديكا, 2020)
Keywords: Hâra, mosquée al- (Sedouikech, Djerba); Monuments -- Djerba; Talâkin, Mosquée (Ghizen, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba)

La spatialité des mosquées ibadites de l'ile de Jerba et de la pentapole du M'Zab au temps de izzaben, étude spatio-syntaxique - Ben Younes, Houda (Ecole Nationale d’Architecture et d’Urbanisme de Tunis, 2018)
Keywords: Ammi Yathi, mosquée (Fahmine, Djerba); Architecture -- Djerba; Architecture -- Mzab; Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Wiran, mosquée (Ajim, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba)

Résistance et dévotion: Anciens sanctuaires ibadites de Djerba - Prevost, Virginie (British Institute for Libyan and Northern African Studies, 2023)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Umar, mosquée (Ghizen, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Attushi, mosquée al- (Wersighen, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Wiran, mosquée (Ajim, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Faqih Umar, mosquée al- (Ajim, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Majlis, Mosquée al- (Guellala, Djerba); Malāq, mosquée (Oued Zbib, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Mihrab Gharib, mosquée (Ghizen, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Bu Sa'id, mosquée (Bazim, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba); Yunus b. Taarit, mosquée (Fatou, Djerba)

The Mosques of Djerba Les Mosquées de Djerba - Hallet, Stanley Ira; Djerbi, Ali (Les Editions de l'Université de Carthage, 2009)
Keywords: Architecture -- Djerba; Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba)

مدونة مساجد جربة - المرابط, رياض (المعهد الوطني للتراث, 2002)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Ammi Umar, mosquée (Ghizen, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Attushi, mosquée al- (Wersighen, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Mīmūn, mosquée (Beni Bandou, Djerba); Bin Wiran, mosquée (Ajim, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Faqih Umar, mosquée al- (Ajim, Djerba); Ghazi Mustafa, Burj (Houmt-Souk, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jadīd (Būmallāl), mosquée al- (Boumellal, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Marākshī, mosquée al- (Houmt-Souk, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Mihrab Gharib, mosquée (Ghizen, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Qṣārīn, mosquée (Houmt Souk, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Abd Allah, mosquée (Beni Bandou, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Bu Sa'id, mosquée (Bazim, Djerba); Sidi Bu Sa'id, mosquée (Boumellal, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Ibrahim al-Jumni, mosquée (Houmt Souk, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Sīdī Bin ʿIsā, zaouia (Houmt-Souk, Djerba); Sīdī Būʿakāzīn, mosquée (Houmt-Souk, Djerba); Sīdī Msāhil, mosquée (Beni Bandou, Djerba); Sīdī Sālim, mosquée (Khanfous, Djerba); Sīdī Zītūnī, zaouia (Houmt Souk, Djerba); Sīdī al-Baḥrī, mosquée (Houmt-Souk, Djerba); Sīdī ʿAbd al-Qādir, zaouia (Houmt-Souk, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Turuk, mosquée al- (Houmt Souk, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Ḥashānī, mosquée al- (Ghizen, Djerba)

مؤنس الأحبة في أخبار جربة - أبو راس, محمد (المعهد القومي للآثار والفنون, 1960)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Monuments -- Djerba; Muʻaskarī, Muḥammad ibn Aḥmad al-, 1737-1823; Récits de voyage -- Djerba; Shaykh, mosquée al- (Guechaine, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba)

جربة جزيرة المساجد - جمعية صيانة جزيرة جربة (الشركة التونسية لفنون الرسم, 1997)
Keywords: Ammi Yathi, mosquée (Fahmine, Djerba); Architecture -- Djerba; Ben Biyan, mosquée (Majmaj, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

تنظيم المجال والتوطين والتعمير بجزيرة جربة في العهد الوسيط أطروحة الدكتوراه في علوم التراث - بربو, المنصف (كلية العلوم الانسانية والاجتماعية, 2017)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba)

التعمير بجزيرة جربة خلال الفترة الوسيطة شهادة الماجستير في الآثار الإسلامية - بربو, المنصف (كلية العلوم الانسانية والاجتماعية, 2011)
Keywords: Midrâjin, mosquée (Mezraya, Djerba); Monuments -- Djerba; Sidi Salih, mosquée (Bani Bandou, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba)

نظام العزابة عند الإباضية الوهبية في جربة - الجعبيري, فرحات‏ بن علي (المعهد القومي للآثار والفنون, 1975)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Attushi, mosquée al- (Wersighen, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Mihrab Gharib, mosquée (Ghizen, Djerba); Monuments -- Djerba; Qasbiyyin, mosquée al- (Guellala, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba)

علماء جربة، المسمى، رسائل الشيخ سليمان بن أحمد الحيلاتي الجربي في ذكر علماء جربة وأماكن أضرحتهم والحوادث التي وقعت في أيامهم ومجالسهم العلمية‏ رحمهم الله تعالى - الحيلاتي, سليمان بن أحمد (دار الغرب الإسلامي‏, 1998)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Umar, mosquée (Ghizen, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Attushi, mosquée al- (Wersighen, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Wiran, mosquée (Ajim, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Faqih Umar, mosquée al- (Ajim, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Mihrab Gharib, mosquée (Ghizen, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Bu Sa'id, mosquée (Bazim, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba); Yunus b. Taarit, mosquée (Fatou, Djerba); Ḥīlātī al-Ğarbī, Sulaymān ibn Aḥmad al- (16..-1688)

تاريخ جزيرة جربة ومدارسها العلمية - بن يعقوب, سالم (سراس للنش, 2006)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Attushi, mosquée al- (Wersighen, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Wiran, mosquée (Ajim, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba); Yunus b. Taarit, mosquée (Fatou, Djerba)

Monographie de l’île de Djerba - Brulard, Armand (Typographie & Lithographie Ch. Delagrange, 1885)
Keywords: Monuments -- Djerba; Récits de voyage -- Djerba; Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

Une lecture de l’histoire moderne des ibadites de l’île de Djerba - Merimi, Mohamed (Horizons maghrébins, 2017)
Keywords: Lîmis, mosquée (Ajim, Djerba); Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba)

Une famille maraboutique de Jerba au xviiie siècle: Son rôle dans l’articulation des communautés locales avec les pouvoirs extérieurs - Merimi, Mohamed (Villes et territoires au Maghreb, 2000)
On the Jumnī family, and on the growing influence of the Mālikīs to the detriment of the Ibāḍīs
Keywords: Ghuraba, mosquée al- (Houmt Souk, Djerba); Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba); Vie politique -- Djerba

Une famille maraboutique de Jerba au xviiie siècle - Merimi, Mohamed (Être notable au Maghreb, 2006)
Keywords: Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba); Vie politique -- Djerba

Monographie de l’île de Djerba - Brulard, Armand (Jerba une île méditerranéenne dans l’Histoire. Recueil de notes, articles et rapport anciens, 1982)
Keywords: Monuments -- Djerba; Récits de voyage -- Djerba; Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

Djerba and the Limits of Rustamid Power. Considering the Ibāḍī Community of Djerba under the Rustamid Imāms of Tāhert (779-909CE) - Love Jr, Paul M. (Al-Qantara : Revista de Estudios Arabes, 2013)
This article is aimed at analyzing the medieval and modern source material dealing with the history of Djerba under the Rustamid Imāmate in an attempt to clarify the nature of both the historical and historiographical relationship between them. It will begin by discussing the available primary and secondary source material, including the historiographical challenges they present. An analysis of the textual and archeological evidence connecting the Rustamids and Djerba will follow. Next, it will attempt to synthesize the scattered bits of evidence available in the historical record in an effort to present a clearer picture of Djerba in the Rustamid period. On the basis of this textual and archeological evidence, it will be argued that Djerba was home to an ibādī community independent of the government in Tahert for the majority ‒if not all‒ of that Imāmate’s existence ‒distinguishing the island from the surrounding areas of the Djerid (in southern Tunisia), parts of Aghlabid Ifrīqiya and the Jebel Nafūsa. Furthermore, it will be shown that evidence suggests this independence was not only a political, but also a religious one. Este ensayo analiza las fuentes de origen medieval y moderno sobre la historia de Ŷarba en el Imāmato rustamí en un intento de aclarar la naturaleza de la relación histórica e historiográfica entre ellos. Se empieza por discutir las fuentes primarias y secundarias disponibles, incluyendo los retos historiográficos que plantean y se presenta a continuación un análisis de las evidencias textuales y arqueológicas que conectan a los rustamíes con Ŷarba. Se intenta después sintetizar las piezas dispersas de la evidencia disponible en el registro histórico con el fin de presentar una imagen más clara de Ŷarba durante el período rustamí. Con base en esta evidencia textual y arqueológica, se argumentará que Ŷarba era hogar de una comunidad ibādí independiente del gobierno en Tāhert durante la mayor parte (si no en su totalidad) de la existencia del Imāmato, distinguiendo así la isla de los alrededores del Ŷarid (en el sur de Túnez), partes de la Ifrīqiya Aglabí y el Ŷabal Nafūsa. Se muestra por último que la evidencia sugiere que esta independencia no era solamente política, sino religiosa.
Keywords: Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba)

L’architecture ibadite - Ben Tanfous, Aziza (IFRIQIYA: treize siicles d'art et d'architecture en tunisie., 2000)
Keywords: Architecture -- Djerba; Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba)

The radicalization of heritage in Tunisia - Rey, Virginie (International journal of Islamic architecture, 2018)
Since the so-called 'Jasmine Revolution' of 2009 in Tunisia, the idea of heritage has been destabilized following a series of attacks on religious and cultural sites across the country by militant Salafi groups. Thus far, sites of Jewish heritage have been the most affected. Cultural heritage from Tunisia's rich ancient history, redolent for certain Islamists with associations of Jahiliyya, has also been targeted. The well-publicized attack on the Bardo Museum in March 2015 was perhaps the most famous symbol of this trend. However, less publicized have been attempts to reclaim some sacred sites, resulting in the occupation of local mosques on the island of Djerba and in the town of Le Kef. In the wake of these events, some Djerbian civilians have stood up to defend what they consider as intrinsic parts of the patrimonial identity of their island. But as they have been defending these mosques against extremist groups, new considerations related to their preservation have surfaced, calling into question their very patrimonialization. In the context of this radical politicization of Tunisian heritage, this article explores the struggle over who defines the meanings and uses of heritage in Tunisia and the new challenges and opportunities that Salafi attacks have created for the heritage sector since the revolution.
Keywords: Architecture -- Djerba; Monuments -- Djerba; Talâkin, Mosquée (Ghizen, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

Les Mosquées de Djerba - Berrebi, Jeannine (Point Dix-sept, 1995)
Keywords: Ammi Yathi, mosquée (Fahmine, Djerba); Architecture -- Djerba; Awlad Hilal, mosquée (Khazroun, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Basi, mosquée al- (Oualegh, Djerba); Bin Hammuda, mosquée (Jaabira, Djerba); Buzid, mosquée (Mellita, Djerba); Buziri, mosquée (Midoun, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Fadhloun, mosquée (Midoun, Djerba); Haddada, mosquée (Midoun, Djerba); Hadharbash, mosquée (Midoun, Djerba); Hajjiyya, mosquée (guellala, Djerba); Jadariyya, mosquée al- (Jaabira, Djerba); Jadid, mosquée (Erriadh, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Majlis, Mosquée al- (Guellala, Djerba); May, mosquée al- (El May, Djerba); Monuments -- Djerba; Mughzal, mosquée (Beni Maaguel, djerba); Qallal, mosquée al- (Oualegh, Djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Qashlin, mosquée (Guechaine, Djerba); Sallawuti, mosquée al- (Midoun, Djerba); Saturi, mosquée al- (Sedouikech, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Sidi Abd al-Qadir, mosquée (Midoun, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Sabbah, mosquée (Midoun, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Sufyan, mosquée (Midoun, Djerba); Tagharghâr, mosquée (Midoun, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Trujit, mosquée (Midoun, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Walḥī, mosquée (Oued Zbib, Djerba); Washniyya, mosquée al- (Midoun, Djerba)

Djerba: les mosquées ibadites - Derriks, Axel; Prevost, Virginie (Cérès Editions, 2017)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Sitta, mosquée (Sedouikech, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Architecture -- Djerba; Awlad Hilal, mosquée (Khazroun, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Basi, mosquée al- (Oualegh, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Hammuda, mosquée (Jaabira, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Fuzar, mosquée (Sedouikech, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jadariyya, mosquée al- (Jaabira, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Luta, mosquée (Sedouikech, Djerba); Majlis, Mosquée al- (Guellala, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Monuments -- Djerba; Qallal, mosquée al- (Oualegh, Djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Sidi Ismail, mosquée (Fâtû, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Salim, mosquée (Khanfus, djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Walḥī, mosquée (Oued Zbib, Djerba)

L'architecture vernaculaire de Djerba pour une approche sémio-anthropologique - Djerbi, Ali (RMR Editions, 2011)
Keywords: Ammi Yathi, mosquée (Fahmine, Djerba); Architecture -- Djerba; Basi, mosquée al- (Oualegh, Djerba); Fadhloun, mosquée (Midoun, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

The Mosques of Djerba Les Mosquées de Djerba de Stanley Ira Hallet | Livres Blurb France - Hallet, Stanley Ira; Djerbi, Ali (Blurb, 2010)
Keywords: Architecture -- Djerba; Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba)

The Mosques of Djerba - Hallet, Stanley Ira; Djerbi, Ali (Blurb, 2009)
Keywords: Architecture -- Djerba; Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba)

Traditionelle Architektur und islamische Bauten auf Djerba - Müller, Klaus Hansjörg (Université de Munich, 1995)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Muhammad Kammus, mosquée (Hachene, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Umar, mosquée (Ghizen, Djerba); Ammi Yathi, mosquée (Fahmine, Djerba); Architecture -- Djerba; Attushi, mosquée al- (Wersighen, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Faqih Umar, mosquée al- (Ajim, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Mihrab Gharib, mosquée (Ghizen, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Bu Sa'id, mosquée (Bazim, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Jmur, mosquée (El Groo, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba); Walḥī, mosquée (Oued Zbib, Djerba)

L'architecture des mosquées ibadites au M'Zab, à Djerba et en Oman: lecture des principes de conception et de construction - Benkari, Naïma (Université Pierre Mendès France, 2004)
Notre recherche s'intéresse au patrimoine architectural produit par la communauté Ibadite au M'Zab, à Djerba et en Oman. Plus précisément, nous nous interrogeons sur les rapports pouvant exister entre les principales caractéristiques des mosquées de ces trois régions et la jurisprudence Ibadite traitant le domaine de l’architecture " `Imâra " et de l’urbanisme " `Umrân ". Nous avons procédé au relevé, à la description et à l'analyse d’un nombre représentatif de sanctuaires dans les trois terrains considérés. Une approche historique de l'Ibadisme et de ses fondements, en plus d’une recherche exploratoire dans le domaine du droit religieux relatif à la construction et à la gestion de la mosquée, ont permis de constituer le corpus juridique nécessaire pour notre analyse. Enfin, cette recherche a tenté d'esquisser une première Image de ce que peut être une " Mosquée Ibadite " et mettre en valeur le rôle qu'a pu jouer le Fiqh dans la constitution de cette architecture religieuse, tout en ne manquant pas de souligner les distorsions et les dépassements dont témoignent les monuments étudiés par rapport aux principes fixés par les savants religieux. Our Research is about the built Heritage realised by the Ibadites in the M'Zab, Djerba and Oman. More precisely, our interrogations concern the relations that may exist between the typical aspect of the mosques in these three regions and the Ibadi Jurisprudence dealing with architecture "`Imâra" and urban planning "`Umrân". We investigated the architecture as well as the Fiqh works of the Ibadi community. We proceeded to the description of a representative number of mosques in the three regions in question. A historical approach of Ibadism and an exploratory research in the field of Ibadi religious laws, related to the construction and the management of mosques, had been undertaken in order to build up the necessary corpus to our analysis. At last, this research made possible a first "image" of what could be the architecture of an "Ibadi mosque", without ignoring the differences and the overtaking which characterize each region.
Keywords: Monuments -- Djerba; Tâjdît, Mosquée (Fâtû, Djerba); Walḥī, mosquée (Oued Zbib, Djerba)

Les mosquées ibadites du Maghreb - Prevost, Virginie (Revue des mondes musulmans et de la Méditerranée, 2009)
Keywords: Architecture -- Djerba; Bûlaymân, Mosquée (Ja’bîra, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Majlis, Mosquée al- (Guellala, Djerba); Monuments -- Djerba; Talâkin, Mosquée (Ghizen, Djerba); Tâjdît, Mosquée (Fâtû, Djerba)

Les Djerbiens. Une communauté arabo-berbère dans une île d'Afrique française - Stablo, René (S.A.P.I, 1984)
Keywords: Abu Miswar, mosquée (Fahmine, Djerba); Abu Smayil, mosquée (Mezrane, Djerba); Abu Zakariyya Fasil, mosquée (Bani Bandou, Djerba); Ammi Umar, mosquée (Ghizen, Djerba); Bardawi, mosquée al- (Mezrane, Djerba); Ben Biyan, mosquée (Majmaj, Djerba); Bin Ma'zuz, mosquée (Mezraya, Djerba); Bin Wiran, mosquée (Ajim, Djerba); Bin Ya'lâ, mosquée (Erriadh, Djerba); Bin Yakhlaf, mosquée (Guechaine, Djerba); Bûkhtîr, mosquée (Taghdimes, Djerba); Bûlaymân, Mosquée (Cedghiane, Djerba); Bûlaymân, Mosquée (Ja’bîra, Djerba); Faqih Umar, mosquée al- (Ajim, Djerba); Ghuraba, mosquée al- (Houmt Souk, Djerba); Hâra, mosquée al- (Sedouikech, Djerba); Jaddi Isa, mosquée (Robbana, Djerba); Jami al-Kabir, mosquée al- (Hachene, Djerba); Lîmis, mosquée (Ajim, Djerba); Midrâjin, mosquée (Mezraya, Djerba); Mihrab Gharib, mosquée (Ghizen, Djerba); Monuments -- Djerba; Mthaniya, mosquée al- (Ajim, Djerba); Mughzal, mosquée (Beni Maaguel, djerba); Qasbiyyin, mosquée al- (Guellala, Djerba); Shaykh, mosquée al- (Guechaine, Djerba); Shaykh, mosquée al- (Houmt Souk, Djerba); Sidi Abd Allah, mosquée (Mezrane, Djerba); Sidi Bu Sa'id, mosquée (Bazim, Djerba); Sidi Garus, mosquée (Haddada, Djerba); Sidi Khalifa, mosquée (Houmt Arbah, Djerba); Sidi Sabbaḥ, mosquée (Tezdaine, Djerba); Sidi Salama, mosquée (Erriadh, Djerba); Sidi Salih, mosquée (Bani Bandou, Djerba); Sidi Waḥlan, mosquée (Haddada, Djerba); Sidi Yahya al-Yazmirtani, mosquée (Erriadh, Djerba); Sidi Zakri, mosquée (Mezraya, Djerba); Sidī Yaʿīsh, mosquée (Jaabira, Djerba); Talâkin, Mosquée (Ghizen, Djerba); Tghazwisan, mosquée (Mezrane, Djerba); Tâjdît, Mosquée (Fâtû, Djerba); Tîfarrûjîn, mosquée (Oualagh, Djerba); Tîwâjin, mosquée (Tîwâjin, Djerba)